772 TREATMENT DECISION MAKING DURING THE OUTPATIENT CLINIC VISIT IN PATIENTS DIAGNOSED WITH ESOPHAGOGASTRIC CANCER, A MIXED METHOD DESIGN. (17th September 2021) - Luijten, Josianne; Brom, Linda; Nieuwenhuijzen, Grard; Westerman, Marjan; Vissers, Pauline; Verhoeven, Rob
Abstract:  : The probability of undergoing treatment with curative intent according to the hospital of diagnosis has been shown to vary considerately for esophagogastric cancer. Little is known about which factors attribute to practice variation. The aim of this study is to investigate the possible differences in treatment decision-making (TDM) after the Multi-Disciplinary Team Meeting (MDTM) advice. Methods: To gain in-depth understanding of TDM quantitative data was gathered by the Netherlands Cancer Registry (i.e., proposed treatment and received treatment) and clinician's and patient's perspectives were assessed. In eight hospitals, 26 outpatient clinic consults were observed, 30 in-depth interviews with clinicians were conducted, and 3 focus groups with patients were conducted. In addition, focus groups with clinicians were held to enrich and further explore the gathered data. Thematic content analysis approach was used. Results: Surgery with curative intent was proposed during the MDTM in 63%, 65% and 72% in patients diagnosed with esophageal cancer in a hospital with respectively low, middle, or a high probability of undergoing treatment with curative intent, respectively. For gastric cancer this was 75%, 82%, 82%, respectively. Changes in the MDTM proposal and received treatment occurred rarely. Clinicians held similar opinions regarding TDM, however its implementation into practice varied. Differences consisted of discussing all treatment options versus only the most fitting treatment option, and the thoroughness of discussing the benefits and harms. Most patients wished to undergo treatment with curative intent. Conclusion: Differences in the believes and personalities of the attending clinicians might attribute to variation in TDM. Variation in practice according to the hospital of diagnosis was mainly observed in the MDTM proposal as hospitals with a high probability of undergoing treatment with curative intent proposed surgery more often. Changes in the MDTM proposal and received treatment occurred rarely.